BEST LINEAR UNBIASED SCALAR (BLUS) RESIDUAL PADA REGRESI LINIER BERGANDA - RENNY ANGGRAENI, 089511307 (2001)
THIS PAPER CONTAINS ABOUT HOW TO USED OF BEST LINEAR UNBIASED SCALED (BLUS) METHOD, WHICH MAKES UNCORRELATED TO MULTIPLE LINEAR REGRESSION.